Chronic Low-Level Lead Exposure Increases Mesenteric Vascular Reactivity: Role of Cyclooxygenase-2-Derived Prostanoids - Simões, Maylla Ronacher; Azevedo, Bruna Fernandes; Alonso, María Jesús; Salaices, Mercedes; Vassallo, Dalton Valentim (Frontiers in Physiology, 2021)
Lead (Pb) exposure causes hazardous effects as hypertension and other cardiovascular diseases. We evaluated whether chronic Pb exposure alters the peripheral vascular resistance measuring the vascular reactivity of mesenteric resistance arteries in rats to identify the underlying mechanisms that are associated to the development of Pb-induced hypertension. Mesenteric resistance arteries from lead-treated and untreated Wistar rats (1st dose: 10 μg/100 g; subsequent doses: 0.125 μg/100 g, intramuscular, 30 days) were used. Contractile responses to phenylephrine increased, while acetylcholine and sodium nitroprusside-induced relaxation was not affected by lead treatment. Endothelium removal and inhibition of NO synthase by L-NAME similarly enhanced the response to phenylephrine in untreated and lead-treated rats. The antioxidants apocynin and superoxide dismutase (SOD) did not affect vasoconstriction in either group. The vascular expression of cyclooxygenase-2 (COX-2) protein increased after lead exposure. The respective non-specific or specific COX-2 inhibitors indomethacin and NS398 reduced more strongly the response to phenylephrine in treated rats. Antagonists of EP1 (SC19220), TP (SQ29548), IP (CAY10441) and angiotensin II type 1 (losartan) receptors reduced vasoconstriction only in treated rats. These conclusions present further evidence that lead, even in small concentration, produces cardiovascular hazards being an environmental contaminant that account for lead-induced hypertension.